Time - Adrian M. Schnall (Case Western Reserve University, 2024)
Time My index finger was reaching for  the up button on the elevator  when the voice sounded above,  Code Blue Tower 8. Code Blue Tower 8. I broke for the stairs.    They were getting the paddles in place;  the First Year with the floppy hair, Ethan,  pumping the chest; the Night Float, Emily, manning an Ambu-Bag; Jamie, the Resident, running the code.   I dared a look at the face -  Ken, with whom I'd traded jokes  for twenty years - Ken, whom I'd told  yesterday his time was coming -  he'd be back home, maybe two days.   Clear! barked Jamie. Hands backed away, motion suspended. A very long second. The shape on the bed gave a shudder. Then Jamie's voice: Excellent, a rhythm.   A rhythm - but no pulse. Hands were pumping again,  counting, squeezing in air.  The spark was there on the screen -  life, dancing across it -  but none of the tiny muscles  in the heart were listening.    Epi. Atropine. Thirty minutes.  Ethan looked up at Jamie, she  shot a glance at me. Someone  had to say it - and first  right of refusal to the guy  with gray hair.   A power none of us wished for -  a power none of us have -  but the world pretends.   I felt my head move up and down. Jamie's eyes found the clock -  7:44 AM, she said. Time.